The Influence of Financial Strategy, Risk Management, and Synergy Mechanisms on Corporate Sustainability - Zhang Zhiquan; Ridwan Nurazi; Willy Abdillah; Berto Usman; Muhartini Salim (West Science Business and Management, 2026)
This study is grounded in stakeholder theory and sustainability theory, which assert that corporate sustainability is determined by an organization’s ability to effectively manage financial strategies, risk, and integrated synergy across organizational units. Although prior literature has examined the role of financial strategy and risk management in influencing corporate performance, studies that simultaneously investigate the combined effects of these variables while incorporating synergy mechanisms as a mediating factor in corporate sustainability remain limited. Addressing this research gap, the present study aims to analyze the influence of financial strategy and risk management on corporate sustainability with synergy mechanisms serving as a mediator. The findings indicate that both financial strategy and risk management have a positive and significant effect on corporate sustainability and play a critical role in strengthening organizational synergy mechanisms. Furthermore, synergy mechanisms are shown to contribute positively and significantly to corporate sustainability and effectively mediate the relationships between financial strategy and corporate sustainability, as well as between risk management and corporate sustainability. These findings underscore the importance of an integrated and collaborative strategic approach in promoting long-term corporate sustainability.